ULMINIUM ATLANTICUM N. SP. TRONCO PETRIFICADO DE LAURACEAE DEL EOCENO DE BAHIA SOLANO, CHUBUT, ARGENTINA (Ameghiniana, 2013)
A new petrified Lauraceous wood is here studied. It is characterized by 1) Diffuse-porosity; 2) Short radial multiple pores; 3) Simple perforation piates; 4) Short vessel member at narrow diameter with mostly alternate pitting; 5) Vasicentric psrenchima sometimes aliform and locally confluent; 6) Low wood rays, l-z-seriate, hetercgcncous, II B (Kribbs ): 7) Narrow fibres with thin wall; 8) Few cells with contens, only piesent in the ray cells; 9) Parenchymatic structures of doubtful interpretation. The new specie s has been compared with living material, mainly from the Southern Hemisphere and Arr.er.ca. Its closest affinities are with the genus Persea, specially P. lingue. Comparisons have been made with 22 fossil species which were selected according the following criteria: a) Havi.ng sorne similar features; b) From Eocene beds; e) From the Southern Hemisphere; d) From Arner.ca. The closest species seem to be Laurinoxylon aromaticum and L. wilcoxianum Berry. Finally, the probable ecological conditions indicated by the fossil are discussed. It is suggested that U. atlanticum belonged to a temperate forest, perhaps with abundant rainfall.